STRATEGI TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN (TJSL) DALAM MANAJEMEN REPUTASI DI KAWASAN BUFFER ZONE PT PUPUK KALIMANTAN TIMUR - Rachel Paskah Yokibeth Tarihoran; Yanuar Luqman (Interaksi Online, 2026)
This study examines the Corporate Social and Environmental Responsibility (TJSL) strategy of PT Pupuk Kalimantan Timur in managing corporate reputation within the buffer zone area. The research adopts a qualitative approach with a case study design under a constructivist paradigm. Data were gathered through in-depth interviews with informants from the TJSL Department of PT Pupuk Kalimantan Timur, alongside field observations and documentation of corporate records and TJSL program reports. Analysis was carried out using time series and pattern matching techniques, grounded in three theoretical frameworks: Legitimacy Theory, Stakeholder Theory, and Institutional Theory. The findings show that PT Pupuk Kalimantan Timur implements its TJSL through four main strategic pillars: (1) community empowerment programs in the buffer zone, (2) environmental conservation, (3) transparent public communication, and (4) active stakeholder involvement in program evaluation. Across all three theoretical lenses, the company's TJSL approach consistently emerges as a structured communication strategy to build social legitimacy, sustain corporate reputation, and secure community support for the company's continued operations in the buffer zone area.